Social and Policy Determinants of COVID-19 Infection Across 23 Countries: An Ecological Study - Kyungsik Kim; Young-Do Jeung; Jeoungbin Choi; Sue K. Park (Korean Society for Preventive Medicine, 2022)
Objectives This study aimed to identify the social and policy determinants of coronavirus disease 2019 (COVID-19) infection across 23 countries. Methods COVID-19 indicators (incidence, mortality, and fatality) for each country were calculated by direct and indirect standardization. Multivariable regression analyses were used to identify the social and policy determinants of COVID-19 infection. Results A higher number of doctors per population was related to lower incidence, mortality, and fatality rates of COVID-19 in 23 countries (β=−0.672, −0.445, and −0.564, respectively). The number of nurses/midwives per population was associated with lower mortality and fatality rates of COVID-19 in 23 countries (β=−0.215 and −0.372, respectively). Strengthening of policy restriction indicators, such as restrictions of public gatherings, was related to lower COVID-19 incidence (β=−0.423). A national Bacillus Calmette-Guérin vaccination policy conducted among special groups or in the past was associated with a higher incidence of COVID-19 in 23 countries (β=0.341). The proportion of the elderly population (aged over 70 years) was related to higher mortality and fatality rates (β=0.209 and 0.350, respectively), and income support was associated with mortality and fatality rates (β=−0.362 and −0.449, respectively). Conclusions These findings do not imply causality because this was a country-based correlation study. However, COVID-19 transmission can be influenced by social and policy determinants such as integrated health systems and policy responses to COVID-19. Various social and policy determinants should be considered when planning responses to COVID-19.